Does oral contraceptive use affect maximum force production in women?. Issue 1 (23rd December 2004) - Elliott, K J; Cable, N T; Reilly, T
Abstract : Objective: To examine the effects of oral contraceptive use on maximum force production in young women. Methods: In the study, 21 female subjects (14 pill users and seven eumenorrheic controls) took part. All pill using subjects had been taking a combined, monophasic oral contraceptive pill for at least 6 months. Maximum dynamic and isometric leg strength, maximum isometric strength of the first dorsal interosseus (FDI) muscle, and plasma concentrations of oestradiol and progesterone were measured on days 7 and 14 of pill consumption and day 5 of pill withdrawal. The eumenorrheic group was tested (FDI strength and hormone concentrations) on days 2 and 21 of the menstrual cycle. Results: There were no significant changes in the concentration of endogenous oestradiol or progesterone or any measure of muscle strength between pill phases (p<0.05). The pill group did not significantly differ from the eumenorrheic group (p<0.05), despite a significant increase in the concentration of progesterone and oestradiol on day 21 of the menstrual cycle compared with day 2 of the menstrual cycle and pill consumption and withdrawal (p<0.05). Conclusions: These data suggest that oral contraceptive use does not significantly affect muscle strength. Moreover, oral contraceptive users were not stronger or weaker than their eumenorrheic counterparts.